Multi-drug-resistance in newly identified patients with tuberculosis in the Sakha Republic (Yakutia) - L. P. Yakovleva; S. N. Kondakov; O. D. Kondratieva; Л. П. Яковлева; С. Н. Кондаков; О. Д. Кондратьева (Acta Biomedica Scientifica, 2018)
Epidemiological process of tuberculosis (TB) in the Sakha Republic (Yakutia) has been characterized by growing incidence of M. tuberculosis (MTB) multidrug-resistance (MDR). This study aimed to explore the incidence of primary MDR in patients with pulmonary TBin Yakutia from 2011 to 2016. Rates of primary MDR (including extensively drug resistant (XDR) cases) incidence were analyzed in new patients with sputum- and/or culture-positive pulmonary TB for Yakutia, Yakutsk, rural regions of Yakutia, and 5 major territorial zones of Yakutia, through theyears 2011 to 2016. We observed an increase from 23 % to 25 % in the proportion of pulmonary TB among primary MDR cases in Yakutia, for the study period. In 2016, this proportion was 1.1 times higher than in Russia (23.4 %), but lower than in the Far East Federal District (25.7 %). In Yakutsk, the same proportion has increased by half (from 24.2 to 35.4 %); in rural regions, on the contrary, it decreased by half (from 21.9 to 14.9 %). Primary MDR percentages among new cases of pulmonary TB decreased in South Yakutia and West Yakutia zones (by factors of 6.7 and 1.6, respectively); same proportions in the Arctic and Central Yakutia zones changed insignificantly. In East Yakutia zone, no case of primary MdR was detected in 2016. XDR cases among new pulmonary TB cases were solitary in 2011, detected only in Yakutsk. During the study period, incidence of XDR among new pulmonary TB cases increased from 0.5 % to 1.7 %, and cases with primary XDR were detected in Yakutsk and Arctic zone. В Республике Саха (Якутия) развитие эпидемического процесса туберкулёза характеризуется ростом множественной лекарственной устойчивости (МЛУ) возбудителя. Целью настоящего исследования явилось изучение динамики показателей первичной МЛУу больных туберкулёзом органов дыхания (ТОД) в РС (Я) в период с 2011 по 2016 годы. Проведён анализ частоты МЛУ возбудителя у впервые выявленных больных ТОД с бактериовыделением и динамики заболеваемости туберкулёзом с МЛУ в РС (Я), г. Якутске и районах ...